The New World Order: Fall of Unilateralism and the Rise of Pluralism - ALYEH, RAGHDA (İstanbul Kültür Üniversitesi, 2023)
After World War II in 1945 and the fall of the Soviet Union in 1991, the United States remains militarily and economically a powerful nation-state; American soft power has also helped to establish democratic principles, universal human rights, and world order. However, the liberal international order or western values promoted by the USA and Europe under which international norms operate are threatened. Norms like sovereignty and territorial integrity, international humanitarian law, democratic values, and economic liberalism are under risk. Rising powers like China, India, and Russia challenge US hegemony in world politics. The inability of the US to stop Iran from developing its nuclear program, Russian invasion of Ukraine, China-Taiwan tensions, the failure of American troops in Afghanistan, the American failure to end the war in Syria, etc. demonstrate how US hegemonic power is in decline. This research will investigate economic, political, and social factors behind the fall of unilateralism and the rise of pluralism. This research will have four chapters. Naturally, chapter one will include an introduction to the topic, a research question, hypotheses, the methodology to gather and analyze data, the significance or importance of the study, and the theoretical framework within which the arguments will be based. Chapter two will present a literature review about the decline of the USA hegemony to formulate a research gap. Chapter three, the most important chapter, will constitute the analysis of the work. We will test our hypotheses in chapter three. And then chapter 4 will be the concluding chapter and recommendations.
Yeni Dünya Düzeni: Tek Taraflılığın Düşüşü ve Çoğulculuğun Yükselişi
▪ Yüksek lisans tezi.
Keywords: Hegemony; International Relations; Pluralism; Soft Power